2019
DOI: 10.1038/s41598-019-50099-y
|View full text |Cite
|
Sign up to set email alerts
|

Distinct gene expression profiles between primary breast cancers and brain metastases from pair-matched samples

Abstract: Our objectives were to determine whether clinic-pathological markers and immune-related gene signatures in breast cancer exhibit any change upon brain metastasis and whether previously reported genes significantly associated with brain metastases and the epithelial-mesenchymal transition (EMT) were reproducible and consistent in our dataset. Sixteen pair-matched samples from primary breast cancers and brain metastases diagnosed were collected from the Japan Clinical Oncology Group Breast Cancer Study Group. Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
552
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(557 citation statements)
references
References 33 publications
(46 reference statements)
5
552
0
Order By: Relevance
“…The confusion matrix ( Supplementary Figure 3) further delineates the shared gene expression signatures between primary and metastatic tumors. This result agreed with earlier studies that have also shown majority genes' expression of primary and metastasized tumors resemble each other [23][24][25].…”
Section: Predicting Types Of Unseen Primary and Metastatic Tumors Witsupporting
confidence: 93%
“…The confusion matrix ( Supplementary Figure 3) further delineates the shared gene expression signatures between primary and metastatic tumors. This result agreed with earlier studies that have also shown majority genes' expression of primary and metastasized tumors resemble each other [23][24][25].…”
Section: Predicting Types Of Unseen Primary and Metastatic Tumors Witsupporting
confidence: 93%
“…In agreement with the findings of other studies, we have identified a number of differences between the primary tumor and metastatic transcriptomes (29,30,32,33). However, by combining data from several models, we show that more significant differences exist in the gene expression between models than between primary tumors and matched metastases, and in fact model may play a larger role in shaping the metastatic transcriptome than tissue type or oncogenic driver.…”
Section: T1supporting
confidence: 91%
“…The incidence of brain metastases in cancer patients is rising, which may be due to the improvements in systematic therapies to control extracranial disease and prolong the survive of patients. Thus, patients who previously may have died sooner from other manifestations of the disease may develop brain metastases [1]. Breast cancer is the second most common cause of brain metastases following lung cancer [2].…”
Section: Introductionmentioning
confidence: 99%